Thin layer chromatography of nucleotides found in Phillipine prawns. - Guiang, Ginna S. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1986)
The dominant pathway of ATP-degradation in two species of Philippine shrimps was ascertained. Samples of panaeus monodon and metapenaeus ensis, after storage in ice and freezer, respectively, were extracted for their nucleotides periodically. Qualitative determinations of these compounds were done utilizing thin-layer chromatography on ion-exchange sheets. Change in the amounts of nuclleotides as storage progressed was determined by the intensity of spots in the development plates. The dominant pathway of P. monodn and M. ensis was through IMP rather than adenosine, under the said storage conditions. However, further studies on these two spp. Of shrimps and their degradation pathway of ATP are recommended since no Hypoxanthine was found to present during the entire storage period.
Keywords: Fish-Processing.